Insights Into Oil Palm Yield Under Seasonal Rainfall - Ijop, Admin; Rao, Vengeta; N, Nuttapong; P, Baskaran; T, Palat (International Journal of Oil Palm, 2024)
Young oil palms produce many small fruit bunches. With age, bunch number (BN) declines but single bunch weight (BW) increases, more than the BN decline, raising its yield (FFB, or BN*BW). In a long-term trial in seasonal Southern Thailand, the age trend accounted for 81% of the variation in BN. With irrigation, BN increased 34%, and BW 5%, and the age trend accounted for 90% of BN variance. It was 98% for BW with/without irrigation. Besides age trends, the regular December – March dry season, despite irrigation, combined with intrinsic alternating sex cycles resulted in annual cycles in BN and BW. The BN cycle was more marked in younger palms whose rooting is shallower. The BW cycle persisted throughout, albeit at lower amplitude than BN. Female abortion after high production resulted in a BN semi-annual cycle, with peaks in Mar/Apr and Sep/Oct. A similar cycle for BW in older palms, with peaks in Dec - Feb and Jun-Aug, arose from fluctuating pollination. A three-year cycle in BN of unirrigated palms may be due to exhaustion/replenishment of carbohydrate reserves. Underripe harvesting, causing more yield in a month, and a dearth after, resulted in a 2-month cycle for BN.